PENGARUH KECURANGAN LAPORAN KEUANGAN, KINERJA KEUANGAN DAN SUSTAINABILITY DISCLOSURE TERHADAP NILAI PERUSAHAAN - Purwanto, Dwi; Lastanti, Hexana Sri (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
This study aims to determine the impact of financial statement fraud, financial performance and sustainability disclosure on firm value. Using financial data from technology companies listed on the Indonesia Stock Exchange between 2020 and 2023, this study employs a panel data regression method. The results of this study are show that financial statement fraud has a negative impact on firm value, while financial performance proxied by profitability ratios and solvency ratios has a positive impact. However, financial performance proxied by liquidity as well as sustainability disclosure actually has a negative impact, which indicates that investors in Indonesia have not fully considered sustainability reports in firm value.